THE USE OF SOCIAL NETWORKS AS AN EDUCATIONAL TOOL IN THE MEANINGFUL ORGANIZATION OF STUDENTS’ LEISURE TIME - Xakimova Marxabo O‘raqovna (Innovate Conferences, 2025)
The article highlights the role of social networks in the meaningful organization of students’ leisure time and the possibilities of using them as an educational tool. The positive and negative aspects of digital platforms, which have become an integral part of the life of today’s youth, are analyzed. Also, recommendations are given on the formation of ideological immunity in students and effective methods of intellectual and moral education through social networks.
Keywords: Students, leisure time, social networks, educational tool, digital environment, ideological immunity.